Low activity of lytic pelagiphages in coastal marine waters - Alonso-Sáez, Laura (ISME J, 2018)
Phages infect marine bacteria impacting their dynamics, diversity and physiology, but little is known about specific phage–host interactions in situ. We analyzed the joint dynamics in the abundance of phage-related transcripts, as an indicator of viral lytic activity, and their potential hosts using a metatranscriptomic dataset obtained over 2 years in coastal temperate waters of the NE Atlantic. Substantial temporal variability was identified in the expression levels of different phages, likely in response to host availability. Indeed, a significant positive relationship between the abundance of transcripts from some of the most abundant phage types (infecting SAR11, SAR116 and cyanobacteria) and their putative hosts was found. Yet, the ratio of increase in phage transcripts per host cell was significantly lower for pelagiphages than for the HMO-2011 phage, which infects SAR116. Despite the high abundance of pelagiphages in the ocean, they may be less active than other phage types in coastal waters.